Reflection Techniques: An Alternative in Improving Counselors' Understanding of Client Characteristics - Fitria Umami; Rezki Hariko; Yeni Karneli (Indonesian Counselor Association (IKI), 2022)
Reflection technique is one of the tools used by counselors in understanding the characteristics and conditions of clients. In this case the reflection technique is used to help problems related to self-awareness. The level of self-awareness of each individual varies, ranging from high levels to low levels. But generally what we most often encounter are individuals with low levels of self-awareness and this can also be related to the sense of responsibility of the individual himself, thus if the level of self-awareness is low then the sense of responsibility he has is also low. For this reason, the reflection technique was chosen by the author in understanding the client's characteristics. This reflection technique is one of the counseling techniques that involves thoughts, feelings and experiences for that it will be easier for researchers to get results. If the researcher is able to understand what the client is feeling, a warm relationship will also be established between the parties involved. Clients will feel comfortable to be invited for interviews and discussions of what is going on in him now. That is the importance of the counselor and client to establish a close relationship and even friendship with one another.